2019
DOI: 10.1371/journal.pone.0223620
|View full text |Cite
|
Sign up to set email alerts
|

eNOS-NO-induced small blood vessel relaxation requires EHD2-dependent caveolae stabilization

Abstract: Endothelial nitric oxide synthase (eNOS)-related vessel relaxation is a highly coordinated process that regulates blood flow and pressure and is dependent on caveolae. Here, we investigated the role of caveolar plasma membrane stabilization by the dynamin-related ATPase EHD2 on eNOS-nitric oxide (NO)-dependent vessel relaxation. Loss of EHD2 in small arteries led to increased numbers of caveolae that were detached from the plasma membrane. Concomitantly, impaired relaxation of mesenteric arteries and reduced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…Additionally, an increase in fatty acid uptake was detected in EHD2 knockout adipocytes and mouse embryonic fibroblasts. Detailed electron microscopy and tomography further supported the idea that EHD2 is essential for correct membrane stabilization of caveolae as EHD2-lacking tissues contained large numbers of detached caveolae (Matthaeus et al, 2019 , 2020 ; Fan et al, 2020 ; Webb et al, 2020 ). Additionally, we observed an increased detachment of caveolae due to EHD2 removal resulting in reduced calcium entry and a resultant lack of activated eNOS and NO generation in endothelial cells.…”
Section: Atp Dependent Ehd2 Oligomerization At the Caveolar Neckmentioning
confidence: 89%
See 3 more Smart Citations
“…Additionally, an increase in fatty acid uptake was detected in EHD2 knockout adipocytes and mouse embryonic fibroblasts. Detailed electron microscopy and tomography further supported the idea that EHD2 is essential for correct membrane stabilization of caveolae as EHD2-lacking tissues contained large numbers of detached caveolae (Matthaeus et al, 2019 , 2020 ; Fan et al, 2020 ; Webb et al, 2020 ). Additionally, we observed an increased detachment of caveolae due to EHD2 removal resulting in reduced calcium entry and a resultant lack of activated eNOS and NO generation in endothelial cells.…”
Section: Atp Dependent Ehd2 Oligomerization At the Caveolar Neckmentioning
confidence: 89%
“…Furthermore, it was shown that in 3T3 fibroblasts EHD2 loss can be rescued by other EHD proteins (Yeow et al, 2017 ). However, a global EHD2 knockout mouse did not exhibit the same observations in adipocytes, fibroblasts, or endothelial cells (Matthaeus et al, 2019 , 2020 ).…”
Section: Atp Dependent Ehd2 Oligomerization At the Caveolar Neckmentioning
confidence: 89%
See 2 more Smart Citations
“…In mice, global EHD2 deletion does not affect viability, in contrast with the embryonic lethality of a Notch1 or Dll4 knockout models [54,55]. However, loss of EHD2 has been shown to increase the number of caveolae that were detached from the membrane and significantly reduced production of endothelial nitric oxide, potentially indicating a preference in endothelial function [56]; loss of Notch function has also been associated with reduced endothelial nitric oxide synthase activity [57]. In line with these observations, we observed that EHD2 knockdown resulted in an elevated number of detached caveolae in ECs.…”
Section: Discussionmentioning
confidence: 99%